Syntheses, solid state and solution structures of the palladium(II) complexes of malonamide-derived open-chain and macrocyclic ligands - Gavrish, Sergey P.; Lampeka, Yaroslaw D.; Pritzkow, Hans; Lightfoot, Philip (Dalton transactions, 2010)
The crystal structures of the palladium(II) complexes of the open-chain and macrocyclic ligands PdL1·3H2O, PdL2·6H2O and PdL3·5H2O have been determined (H2L1 = 1,4,8,11-tetraazaundecane-5,7-dione, H2L2 = 1,4,8,11-tetraazacyclotetradecane-5,7-dione, H2L3 = 1,4,8,11-tetraazacyclotridecane-5,7-dione). The coordination polyhedra of the palladium(II) ions in all complexes are formed by two deprotonated amide and two amine donors with Pd-N distances being similar in PdL1 and PdL2 and substantially shorter in PdL3. A detailed analysis of the 1H NMR spectra of the macrocyclic complexes supports the formation in aqueous solution of only N-meso isomers of both compounds in agreement with the X-ray data. The spectra of the palladium(II) macrocyclic complexes are shifted downfield as a whole as compared to those of the nickel(II) analogues with the shifts being essentially non-uniform. The latter feature can be related to the differences in magnetic anisotropy of the M-N bonds. The maxima of d-d absorption bands of the palladium(II) complexes demonstrate weaker dependence on the macrocycle size as compared to those of the nickel(II) analogues. Both macrocyclic compounds PdL2·6H2O and PdL3·5H2O are characterized by lamellar crystal structures consisting of interleaved layers formed by macrocyclic units and by water molecules with similar metal complex layers and different 2D water sheets. A columnar crystal structure is inherent for PdL1·3H2O with the water molecules present as discrete (H2O)3 clusters.
Gesehen am 20.02.2023